From Power to Oppression: Threats to the Security of Afghan Women in the New Era of the Taliban Regime - Bhanuwati, Abhitah Hayu (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
This research aims to analyze the policy impact of the Taliban regime on gender-based violence and its implications for human security in Afghanistan, focusing on the conditions of women and girls. Since the Taliban returned to power in 2021, Afghan women have been systematically oppressed. Gender-based violence has become pervasive in Afghanistan as a result of girls’ limited access to education, limited freedom of movement, and limited job possibilities. Due to their low engagement in public life, women and girls are disproportionately affected by the ongoing humanitarian catastrophe in Afghanistan, which has been made worse by these circumstances. This research was written using qualitative approaches, including the examination of pertinent literature and policy analysis as a means of gathering data. The results of this research demonstrate that women’s physical and emotional safety can be seriously threatened by the Taliban. Additionally, the Taliban obstruct their access to necessities like healthcare and education. The research also demonstrates how the policy has made the environment unwelcoming for women, which has decreased their involvement in all facets of life. This research is expected to add to the scientific debate on gender security policies and will motivate the international community to increase the defense of women’s rights in Afghanistan. The conclusion of this research is that the policies of the Taliban regime have drastically increased gender-based violence and exacerbated the humanitarian crisis in Afghanistan, with devastating effects on the security and well-being of women and girls